A Thick Translation of Hmong Oral Epics from the Perspective of Cultural Anthropology - Fei Wu (RIRAI Publisher, 2022)
Hmong Oral Epics is an oral classic of the Miao people, carrying the cultural memory of the ancient history of the Miao people. The Hmong Oral Epics translated by American sinologist Mark Bender has been praised as